Prognostic value of PD-1, PD-L1, TYMS and DCC in colorectal carcinoma and association with overall and disease-free survival - Onwe, Ebenyi Emeka (2020)
Some biomarkers in CRC are useful for stratifying patients more appropriately for adjuvant treatment and could be used to evaluate patients overall outcome, to monitor chances of recurrence after standard treatment. Co-expression of programmed cell death- 1 (PD-1), programmed cell death- ligand 1 (PD-L1), thymidylate synthase (TYMS), and deleted in colorectal carcinoma (DCC) biomarkers are not widely studied in CRC simultaneously. This study aimed to evaluate PD-1, PD-L1, TYMS, and DCC expression in tissue blocks collected from CRC patients who attend Hospital Serdang, Selangor Malaysia. Ninety one formalin fixed paraffin embedded (FFPE) archival tumour samples from patients who underwent surgical resection, were assessed using mmunohistochemical (IHC) method. There was high expression of DCC detected in 84.6% (77/91) in most cases. TYMS expression at high level was 46.2% (42/91) and low level was 53.8% (49/91) respectively. Majority of cases showed low PD-L1 expression in 93.4% (86/91) and high expression was detected in 6.6% (6/94) of cases. PD-1 expression was low in all cases. There was a significant association between TYMS expression with gender (P < 0.05) with distribution of TYMS expression at high level was 76.2% in male and 23.8% in female. The Kaplan-Meier survival plot showed that overall survival (OS) mean was 94 months and disease free survival (DFS) mean was 110 months. A Log rank test showed there was no statistical significance between PDL1, TYMS and DCC with OS and DSF patients. In conclusion, the results from this study suggest that PD-L1, TYMS and DCC expression could be used as biomarkers to predict treatment outcome in CRC, PD-L1 overexpression predict patients who could benefit from anti-PD-1 and anti-P D-L1 immunotherapy, TYMS low expression predict patients who could benefit from 5-fluorouracil therapy and DCC high expression tumours predicts a better prognosis and overall survival than DCC low expression in advanced CRC.